2017
DOI: 10.1213/ane.0000000000001108
|View full text |Cite
|
Sign up to set email alerts
|

Early Left and Right Ventricular Response to Aortic Valve Replacement

Abstract: Background The immediate effect of aortic valve replacement (AVR) for aortic stenosis on perioperative myocardial function is unclear. Left ventricular (LV) function may be impaired by cardioplegia-induced myocardial arrest and ischemia-reperfusion injury, especially in patients with LV hypertrophy. Alternatively, LV function may improve when afterload is reduced following AVR. The right ventricle (RV), however, experiences cardioplegic arrest without benefiting from improved loading conditions. Which of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…This is particularly important in cardiac surgery patients in whom numerous insults to the right ventricle occur over time (eg, poor preservation with cardioplegia, air, increased pulmonary vascular resistance after CPB), and RV function must be reassessed continually during the prebypass and postbypass periods. 26,27 It is important to note that even though the authors of the present study found both regional and global strain measurements to be highly sensitive for RV dysfunction, the specificity was only moderate. Consequently, a normal RV strain measurement likely rules out dysfunction but an abnormal RV strain sometimes is seen in the setting of a normal RV EF.…”
Section: Discussionmentioning
confidence: 50%
“…This is particularly important in cardiac surgery patients in whom numerous insults to the right ventricle occur over time (eg, poor preservation with cardioplegia, air, increased pulmonary vascular resistance after CPB), and RV function must be reassessed continually during the prebypass and postbypass periods. 26,27 It is important to note that even though the authors of the present study found both regional and global strain measurements to be highly sensitive for RV dysfunction, the specificity was only moderate. Consequently, a normal RV strain measurement likely rules out dysfunction but an abnormal RV strain sometimes is seen in the setting of a normal RV EF.…”
Section: Discussionmentioning
confidence: 50%
“…The basal longitudinal motion is reduced, whereas apical circumferential motion increases [19,20]. The most striking effect after surgical and transcatheter AVR is increased basal longitudinal motion [21][22][23]. The apical region where the accelerometer was placed is less affected [18,21,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that its structure and function is very important in patients with congenital heart disease and pulmonary hypertension, but afterward, the important role of RV remodeling has been proved in the patients with heart failure, heart transplantation, cardiomyopathies, and valvular heart disease . The influence of aortic stenosis (AS) and particularly of AS severity on RV remodeling is still debatable, and the data are scarce . Recently, several studies regarding the prognostic importance of RV structure and function in AS patients after surgical replacement or catheter aortic valve implantation have been published …”
Section: Introductionmentioning
confidence: 99%
“…The influence of aortic stenosis (AS) and particularly of AS severity on RV remodeling is still debatable, and the data are scarce . Recently, several studies regarding the prognostic importance of RV structure and function in AS patients after surgical replacement or catheter aortic valve implantation have been published …”
Section: Introductionmentioning
confidence: 99%